Hydrolysis of soybean 7S and 11S globulins using bacillus subtilis - Han X. (2017)
Soybean protein is an important plant protein source; its two major constituents, 7S and 11S, account for more than 70% of its total protein. in this study, the soybean 7S and 11S fractions were enzymatically hydrolyzed by Bacillus subtilis strains from traditional fermented foods, and the hydrolysates were analyzed using immunoblot ting and an amino acid analyzer. According to the immunoblotting, the main components and allergens of 7S and 11S were degraded into smaller units. Large amounts of free amino acids (FAA) released in diverse profiles were also detected. B. subtilis SB3 and SB5 released more total FAA than other strains. Therefore, these B. subtilis strains may have potential for application in the production of hypoallergenic soybean foods rich in FAA. © 2012 Food Sci. Technol. Res.